A Political Economy of Performance Measurements - Florence Jany-Catrice (Social Work and Society)
In the field of the Welfare State, the evaluation of public policies is more and more becoming a series of small devices (programmes, projects, nudges) aiming at measuring the performance of public services. This transforms the scope of the evaluation process and transforms the way by which"the effectiveness" of social policies is revealed and measured. This paper defends the idea that the claim for "performance" is one of the symptoms of the dissolution of evaluation of public policies in the measurement of the performance of public services. This is also a way of confusing individual performance with social progress.